Inversion and analysis of aerosol optical properties and lidar ratios based on sky-radiometer and Raman lidar measurements in Xi’an, China - Liu, Jingjing; Guo, Zhuqi; Zhou, Luyao; Wang, Longlong; Wang, Jun; Yan, Qing; Hua, Dengxin (Frontiers in Environmental Science, 2022)
The aerosol observations in Xi'an (34.25°N,108.983°E), a typical urban site in Northwest China, were conducted using a sky-radiometer from January 2015 to March 2018. Multi-year variations of aerosol optical properties (AOPs) and lidar ratios (LRs) were simultaneously analyzed and calculated. In particular, LRs in 340 nm were compared and validated using the UV-Raman lidar (RL) measurements. During the study period, aerosol optical depth at 500 nm (AOD500) had significant seasonal variation, with a maximum value of 0.68 in winter and a minimum value of 0.59 in autumn. Ångström exponent (AE) exhibited different seasonal variation patterns, and the minimum (0.81) and maximum (1.06) values appeared in spring and summer, respectively. The spectral difference between AE400–675 and AE675–870 indicated that high AOD675 values (>1.0) were affected by accidental factors (e.g., dust weather in spring and winter) and the accumulation of fine particle aerosols across all seasons. The relationship between AOD500 and AE400–870 was used to distinguish different aerosol types. Overall, mixed aerosols (MX) accounted for the largest contribution (ranging from 40.14% in autumn to 69.9% in spring), followed by biomass-burning or urban/industrial aerosols (BB/UI) (with the smallest value of 19.9% in spring,and the largest value of 43.66% in winter). Single-scattering albedo (SSAs) experienced weak seasonal variation, with a minimum in winter and a maximum in spring. The seasonal aerosol volume size distributions (VSDs) generally exhibited the trimodal patterns. The particle radius (R) of less than 0.5 μm is considered as fine mode, the coarse mode is R greater than 2.5 μm, and the middle mode is located somewhere in between them. The real CRI were ~1.41–1.43, with no significant difference among different seasons. Besides, the LRs derived by combining sky-radiometer with Mie-scattering theory changed greatly with weather from 49.95 ± 8.89 in summer to 63.95 ± 6.77 in autumn, which were validated by RL with the errors within a certain height range of less than 10%. We confirmed the feasibility of using the LR of UV band from sky-radiometer as a reference value for the Fernald or Klett method.